2011
DOI: 10.4103/0974-7761.93413
|View full text |Cite
|
Sign up to set email alerts
|

Use of computers among students of dental college in Saudi Arabia

Abstract: Background:The Riyadh Colleges of Dentistry and Pharmacy (RCSDP) is in the process of implementing a total computer based information system to improve the delivery of curricula, clinical teaching and administration. In order to measure the level of acceptance and the degree of training that would be required, a survey was undertaken to investigate the current knowledge and skills of students with respect to information communication technology (ICT). Materials and Methods: Data collection took place by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…The respondents mentioned Google (62.5%), Wikipedia (39.6%), YouTube (16.7%), Yahoo (12.5%) and Facebook (6.3%) as their mostly visited sites/webs for academic purposes. This simulates closely with that dental college students of Saudi Arabia (Rahman, 2011) and Jordan (Rajab & Baqain, 2005) where PubMed and Hotmail MSN were also the other leading…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The respondents mentioned Google (62.5%), Wikipedia (39.6%), YouTube (16.7%), Yahoo (12.5%) and Facebook (6.3%) as their mostly visited sites/webs for academic purposes. This simulates closely with that dental college students of Saudi Arabia (Rahman, 2011) and Jordan (Rajab & Baqain, 2005) where PubMed and Hotmail MSN were also the other leading…”
Section: Discussionsupporting
confidence: 85%
“…Majority (76.4%) of them used computers for more than 3 years which is similar with a very recently published Saudi Arabian study (Rahman, 2011), but grossly dissimilar with the results obtained from studies in Manchester, Bristol and New Castle of UK, where 20%, 14% and 57% students respectively were reported to use the computer for more than three years (Grigg, 2001). This may be attributed to the fact that these three studies in UK were conducted more than a decade ago and the use of computer might have increased since then.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…[5] Information and communication technology is an increasingly important tool in dental education. [6] Several studies have shown the potential use of computers, IT and internet in dental curriculum as an educational tool.…”
Section: Discussionmentioning
confidence: 99%